2020
DOI: 10.3390/ijerph18010182
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Concentration and Dynamics of Culturable Fungal Bioaerosols at Doha, Qatar

Abstract: This research was conducted to investigate the dynamics of airborne fungi using viable culture collection and in respect to different abiotic variables, including seasonal and intra-diurnal variations. A gravimetric method was used to sample airborne fungal deposition on potato dextrose agar plates on alternate days, for a year between April 2015 to March 2016. From 176 settle plate exposures, a total of 1197 mould and 283 yeast colony-forming units (CFU), 21 genera and 62 species were retrieved. The highest f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Although the air sampling/dust collection during home inspection and the culturable method have been conducted by several studies, 26,63–66 to evaluate the indoor airborne fungal concentrations by quantification, the one‐time air sampling is only helpful to determine current exposure at the sampling location at that time. The results do not facilitate evaluation of long‐term exposure of fungi in air and their dynamic variation temporally and spatially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the air sampling/dust collection during home inspection and the culturable method have been conducted by several studies, 26,63–66 to evaluate the indoor airborne fungal concentrations by quantification, the one‐time air sampling is only helpful to determine current exposure at the sampling location at that time. The results do not facilitate evaluation of long‐term exposure of fungi in air and their dynamic variation temporally and spatially.…”
Section: Discussionmentioning
confidence: 99%
“…The onsite measurements revealed that most studied homes have exposure risks to higher airborne fungal concentrations and medium pollution level (Figure 3). Moreover, the results in Figure 11 studies, 26,[63][64][65][66] to evaluate the indoor airborne fungal concentrations by quantification, the one-time air sampling is only helpful to determine current exposure at the sampling location at that time.…”
Section: Combinations Of Cross-sectional Surveys and Onsite Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current review are similar to many studies from the Middle East. In Doha-Qatar, a total of 21 fungal genera were isolated by gravity method and the predominant taxa were Cladosporium, Aspergillus, Fusarium, Alternaria and Penicillium [43]. Al-Halawgy has found that 74.2% of spore types in Kuwait belong to Deuteromycotina, and Cladosporium was the predominant taxon [44].…”
Section: Occurrence% (O%)mentioning
confidence: 99%